Assessment of Bacteriological Quality of Public Swimming Pool Water in Ile-Ife, Nigeria - C. N. Fakorede; A. A. Olayinka; E. N. Fatokun; A. S. Agbetuyi (Journal of Applied Sciences and Environmental Management)
Swimming pools are important recreational resources in urban areas, contributing to physical fitness, social interaction, and mental well-being. Consequently, the objective of this study is to assess the bacteriological quality of public swimming pool water in Ile-Ife, Nigeria using standard methods. The pH and temperature of the water samples ranged from 7.1 to 7.4, and 23.6oC to 26.5oC respectively. Eight of the ten pools tested positive for bacterial contamination. Six different Gram-negative bacteria (GNB) were isolated, with Escherichia coli (32%), Klebsiella pneumoniae (16%), Salmonella subsp. (12%) and Pseudomonas aeruginosa. (8%), being the most prevalent. The coliform bacteria count ranged from 1.0×10² CFU/100ml to 9.8×10² CFU/100ml and the Salmonella count ranged from 1.0 x 10² CFU/100ml to 3.0 x 10² CFU/100ml. Most of the GNB isolates were resistant to commonly administered antibiotics like Augmentin (62.5%), and ampicillin (57.6%) but were totally susceptible to quinolones and carbapenem. This study highlights the significant public health threat posed by fecal contamination and the presence of antibiotic-resistant bacteria in outdoor swimming pools in Ile-Ife, underscoring the need for improved pool maintenance and monitoring.